Introduction to Western Culture Cultural History, Religion, Politics, Folklore and Tourism (Springer Singapore, 2018)
Promoting cultural understanding in a globalized world, this collection provides a concise and unique introduction to western culture, through the voices of Chinese scholars. Written by a team of experts in their fields, the book starts with an introduction to western philosophy and covers an interdisciplinary range of topics across literature, language, music, art and religion. It addresses such issues as tourism and etiquette, as well as the key differences of distinct cultures, providing readers with a succinct yet effective way to master a basic understanding of Western culture.